2015
DOI: 10.1371/journal.pone.0144034
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Depth Order and Density Affects Vection and Postural Sway

Abstract: ObjectiveVection, a feeling of self-motion while being physically stationary, and postural sway can be modulated by various visual factors. Moreover, vection and postural sway are often found to be closely related when modulated by such visual factors, suggesting a common neural mechanism. One well-known visual factor is the depth order of the stimulus. The density, i.e. number of objects per unit area, is proposed to interact with the depth order in the modulation of vection and postural sway, which has only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…With respect to the current study, vection strength and the magnitude of VEPR change consistently with changes in visual intensity such as the occluding area (Kawakita et al., 2000), stimulus speed (Kuno et al., 1999; Lestienne et al., 1977), and stimulus density (Lubeck et al., 2015).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…With respect to the current study, vection strength and the magnitude of VEPR change consistently with changes in visual intensity such as the occluding area (Kawakita et al., 2000), stimulus speed (Kuno et al., 1999; Lestienne et al., 1977), and stimulus density (Lubeck et al., 2015).…”
Section: Discussionsupporting
confidence: 62%
“…We also measured full-field and hemifield (upper or lower) optic flows. In addition to head movement, we measured perceived vection to check consistency of postural sway with the perception of self-motion (Kawakita et al., 2000; Kuno et al., 1999; Lestienne et al., 1977; Lubeck, Bos, & Stins, 2015), given that this relationship has been challenged (Previc, 1992; Previc & Mullen, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating possible biomarkers for quantifying vertigo and categorizing its severity is of great importance for clinical balance evaluations. There is evidence that an increase in visual density contained in a rotating scene is associated with increased body-sway [14]. In a recent study we have shown how the torsion-skewing ratio is sensitive to changes in visual clutter density, with the eyes exhibiting more degrees of torsion per degrees of skewing in response to increased clutter [11].…”
Section: Introductionmentioning
confidence: 87%
“…While other studies did not obtained all three measures together, most obtained at least one or more of them 4 (e.g., Allison, Zacher, Kirollos, Guterman, & Palmisano, 2012 ; Andersen & Braunstein, 1985 ; Ash & Palmisano, 2012 ; Ash, Palmisano, Apthorp, & Allison, 2013 ; Ash, Palmisano, Govan, & Kim, 2011 ; Ash, Palmisano, & Kim, 2011 ; Becker, Raab, & Jürgens, 2002 ; Brandt, Dichgans, & Büchele, 1974 ; Brandt, Wist, & Dichgans, 1975 ; Delorme & Martin, 1986 ; Diels, Ukai, & Howarth, 2007 ; Fushiki, Takata, & Watanabe, 2000 ; Giannopulu & Lepecq, 1998 ; Haibach, Slobounov, & Newell, 2009 ; Held, Dichgans, & Bauer, 1975 ; Howard & Heckmann, 1989 ; IJsselsteijn, de Ridder, Freeman, Avons, & Bouwhuis, 2001 ; Ishida, Fushiki, Nishida, & Watanabe, 2008 ; Ito & Shibata, 2005 ; Ito & Takano, 2004 ; Ji, So, & Cheung, 2009 ; Jürgens et al., 2016 ; Kano, 1991 ; Kennedy, Hettinger, Harm, Ordy, & Dunlap, 1996 ; Kim & Khuu, 2014 ; Kim, Palmisano, & Bonato, 2012 ; Lubeck, Bos, & Stins, 2015 ; Ohmi & Howard, 1988 ; Ohmi, Howard, & Landolt, 1987 ; Palmisano, 2002 ; Palmisano, Allison, & Howard, 2006 ; Palmisano, Apthorp, Seno, & Stapley, 2014 ; Palmisano, Bonato, Bubka, & Folder, 2007 ; Palmisano, Kim, & Freeman, 2012 ; Palmisano, Mursic, & Kim, 2017 ; Post, 1988 ; Previc...…”
Section: The Opvmmentioning
confidence: 99%